Modified Pb(Mg1/3Nb2/3)O3‐PbZrO3–PbTiO3 ceramics with high piezoelectricity and temperature stability. Issue 10 (24th March 2021) - Wang, Pengbin; Guo, Qinghu; Li, Fei; Xia, Fangquan; Hao, Hua; Sun, Huajun; Liu, Hanxing; Zhang, Shujun
Abstract: There is a great demand to develop ferroelectric ceramics with both high piezoelectric coefficient and broad temperature usage range for emerging electromechanical applications. Herein, a series of Sm 3+ ‐doped 0.25Pb(Mg1/3 Nb2/3 )O3 ‐(0.75− x )PbZrO3 ‐ x PbTiO3 ceramics were fabricated by solid‐state reaction method. The phase structure, dielectric and piezoelectric properties were investigated, where the optimum piezoelectric coefficient d 33 = 745 pC/N and electromechanical coupling factor k 33 = 0.79 were obtained at the morphotropic phase boundary composition x = 0.39, with good Curie temperature T C of 242°C. Of particular importance is that high‐temperature stability of the piezoelectric and field‐induced strain was obtained over the temperature range up to 230°C for the tetragonal compositions of x = 0.40. The underlying mechanism responsible for the high piezoelectricity and temperature stability is the synergistic contribution of the MPB and local structural heterogeneity, providing a good paradigm for the design of high‐performance piezoelectric materials to meet the challenge of piezoelectric applications at elevated temperature. Abstract : Comparison of the d 33 vs. T C diagram and the temperature dependence of normalized strain d 33 ∗ as normalized to its room temperature value d 33 ∗RT